Notes on male and female facial patterns in bees (Hymenoptera: Apoidea), with comments on other aculeates - Michener, Charles D. (Journal of Melittology, 2013)
Pallid (frequently yellow) integumental areas characterize faces of many bees and related wasps.  Some species lack such markings, others lack them only in females, while others have them in both sexes.  A rule applicable to thousands of species is that, if present, yellow areas are more extensive in males than in females.  In different groups, yellow areas can be either expanded or reduced, both have occurred repeatedly in the Aculeata.  In some groups that lack integumental yellow facial areas, males have brushes of yellow or brassy facial hairs that hide the integument.  Behavior associated with presence or abscence of facial yellow areas is not recognized, for mating males usually approach females from above and behind so that neither can see the face of the other.  Possibly male-to-male interactions are involved.